Upper Lip Changes After Upper Incisor Proclination in Deep Bite Patients - Tiamlom, Piyatida; Charoemratrote , Chairat (Thai Journal of Orthodontics, 2025)
Background: No previous studies examined the effects of upper lip (UL) change following upper incisor (UI) intrusion by labial proclination in deep bite (DB) non-growing patients. Objective: To compare changes in the UI and UL after labial proclination between UI retroclination (RI) and normal inclination (NI) groups in DB patients. Materials and methods:Pretreatment (T1) and posttreatment (T2) lateral cephalograms of 41 subjects who underwent UI labial proclination were divided into two groups according to UI inclination: RI group (UI-THL<113°) and NI group (113°≤ UI-THL≤ 119°). Cephalograms used the true horizontal and true vertical lines to measure the UI and UL parameters. Treatment changes were compared both within and between the groups. Results: At T1, the RI group showed significantly more retroclined and retruded UI, increased incisal show at rest (ISR) and overbite compared to the NI group. Soft tissues were comparable, except for thicker lip in RI. At T2, the RI group exhibited normal inclination and position, while greater proclination and protrusion were observed in NI. No significant differences were observed in the ISR, overbite, or soft tissue variables between the groups. The treatment change (T2-T1) in both groups exhibited a significant proclination of the UIs. However, the RI group showed no significant change in the UL, while NI group revealed significant UL protrusion.Conclusion: The UL changes in the RI group did not show significant differences. In contrast, the NI group showed more UL protrusion, although it exhibited lesser proclination of UI compared to RI group.